Issues in Zulu relativization - Poulos, George (Rhodes University, Faculty of Humanities, School of Languages, 1982)
Zulu is a language of the Nguni group of the South-Eastern Zone of Bantu languages and is spoken by approximately 5 400 000 people. As far back as 1848, the Zulu language was investigated by a missionary of the American Board in Natal, James C. Bryant. In that year his ideas on the language were put on paper under the title, The Zulu Language, and this valuable contribution of some 13 pages was published in the following year in the Journal of the Oriental Society . Bryant's work heralded the beginning of a tradition of analysis in Zulu that was to capture the interest of a number of investigators over a period stretching up until the present day.
Keywords: Zulu language -- Relative clauses